Der europäische Qualifikationsrahmen als Integral von Hochschulbildung und beruflicher Bildung: Das Ende des klassischen Universitätsmodells(?) - Dunkel, Torsten [Verfasser] (My University, 2006)
"On the way towards the European Higher Education Area 2010 the EQF proposal by the European Commission offers on the one hand opportunities for increased geographical mobility within higher education and on the other hand enhanced permeability between the HE and VET subsystems, but faces also interface incompatibilities of certifying HE and VET. The further development of the ECTS and ECVET Credit Systems from the transfer to the accumulation function as well as from the input to the outcome orientation shall increasingly promote the mobility of students, apprentices and graduates via the transfer, accumulation and recognition of learning outcomes described in acquired knowledge, skills and competence. This has consequences for the classical university model." (Autorenreferat, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 1.4 Hochschulbildung; G 1.3.3.3 Mobilität; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; EU-Bildungspolitik; Hochschulbildung; Europäischer Bildungsraum; Bologna-Prozess; Mobilität; Durchlässigkeit im Bildungssystem; Europäisches Leistungspunktesystem; Europäischer Qualifikationsrahmen